Comparative analysis of the utilisation of maternal healthcare in rural and urban communities in the Tolon District, Ghana - Buor, Daniel; Agyemang, Seth; Issah, Abubakari- Sadiq (Archives of Clinical and Biomedical Research, 2024)
There are limited research works on a comparative analysis of the utilization of maternal healthcare in rural and urban communities in Ghana and developing countries. The study makes a comparative analysis of the utilization of maternal healthcare in a district in the deprived northern region of Ghana. It attempts a comparative analysis of the differences in the utilization of maternal healthcare in rural and urban communities in an economically deprived region in Ghana. Using a quantitative crosssectional design and a sample of 120 drawn using the accidental sampling design, the disparities in the use of maternal healthcare facilities are assessed with the Andersen (1995) behavioural model serving as the theoretical framework. The main findings are that there is a significant difference between rural and urban participants in the utilization of maternal healthcare with the urban utilizing the services more than the rural. Secondly, the socio-economic factors showing significant differences in the use of maternal healthcare are employment, distance and family support. Thirdly, the urban community uses skilled delivery services more than the rural and education and cost of service do not predict the use of maternal healthcare between the two communities. Despite the policy of free maternal healthcare in the district, the urban community utilizes the services more than the rural. There must be policies to improve the provision of maternal healthcare facilities in rural communities and to educate the rural communities to patronise maternal healthcare.